Návrh dílčí části informačního systému pro vybraný subjekt - Liebscher, Tomáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá analýzou a výběrem vhodného informačního systému pro vybranou firmu. Informační sytém je vybrán dle požadavků firmy a má pomoci k zefektivnění firemních procesů. Provedu analýzu jednotlivých informačních systému na trhu a vyberu ten, který nejvíce odpovídá stanoveným kritériím a požadavkům. Následně navrhnu postup implementace do elektronického obchodu a jejich vzájemnou komunikaci. V závěru je provedeno ekonomické zhodnocení.

The diploma thesis deals with the analysis and selection of a suitable information system for selected company. The information system is selected according to the company's requirements and helps to streamline business processes. I will analyze individual information systems on the market and select the one that most closely matches the set criteria and requirements. I will then propose how to implement e-commerce and how to communicate with each other. At the end, an economic assessment is made.
Proposal of Part of Information System for Selected Subject
Keywords: Informace; data; systém; informační systém; IS; ERP; implementace; moduly; elektronický obchod; Prestashop; Information; data; system; information system; IS; ERP; implementation; modules; ecommerce; Prestashop